2021
DOI: 10.3390/jcm10194368
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prognostic Factors Associated with Good Outcomes in Pediatric Bell’s Palsy

Abstract: The prognosis of children with Bell’s palsy remains unclear due to its relatively low incidence, and thus, the small number of patients included in individual studies. To evaluate the prognosis of children with Bell’s palsy and identify the predictive value of specific factors that contribute to complete recovery, a retrospective cohort study was conducted of all patients with Bell’s palsy who visited the outpatient clinic of our university hospital between January 2005 and December 2020. We identified the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Recent study revealed that the H-B grade II–IV of initial facial nerve paralysis was a significant good prognostic factor. 6 The prognostic value of imaging examination for facial palsy is controversial. A study indicated that the lesion side showed significantly higher signal intensities after contrast agent administration.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study revealed that the H-B grade II–IV of initial facial nerve paralysis was a significant good prognostic factor. 6 The prognostic value of imaging examination for facial palsy is controversial. A study indicated that the lesion side showed significantly higher signal intensities after contrast agent administration.…”
Section: Introductionmentioning
confidence: 99%